2017
DOI: 10.1111/j.1755-3768.2017.01187
|View full text |Cite
|
Sign up to set email alerts
|

Macular thickness after intraocular pressure reduction following trabeculectomy

Abstract: Purpose The aim of the study was to assess changes of macular thickness after trabeculectomy and compare them in respect to the usage of preoperative prostaglandins and status of diabetes mellitus. Methods The prospective observational study included 93 glaucomatous eyes (90 patients) that underwent trabeculectomy. 81 (87.1%) patients were on prostaglandins treatment preoperatively. 5 (5.38%) patients had type 2 diabetes. The foveal and sectoral macular thicknesses were measured preoperatively, 1 week, 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Such findings in terms of the neutral effect of DM status and prostaglandin drops usage on postoperative macular changes were confirmed in another study by Drukteiniene et al . 13 They studied 93 eyes from 90 patients who underwent trabeculectomy and followed them up to 12 months. They found mild macular thickening, which was more pronounced in the early postoperative period (6 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings in terms of the neutral effect of DM status and prostaglandin drops usage on postoperative macular changes were confirmed in another study by Drukteiniene et al . 13 They studied 93 eyes from 90 patients who underwent trabeculectomy and followed them up to 12 months. They found mild macular thickening, which was more pronounced in the early postoperative period (6 months).…”
Section: Discussionmentioning
confidence: 99%
“…8 9 In addition, diabetes mellitus (DM) or prostaglandin drops usage before surgery has not been shown to have any impact on these postoperative macular changes. 8 13 However, some studies have shown that early postoperative changes in macular thickness can be different, defined by spectral domain-optical coherence tomography (SD-OCT), in different quadrants of the macula. 14 …”
Section: Introductionmentioning
confidence: 99%
“…As a clinically researched blinding disease, glaucoma tends to cause vision loss and even blindness in patients, and studying the physiological and pathological reactions in glaucoma has important implications for the clinical treatment of glaucoma. Acute high intraocular pressure, one crucial pathological process in glaucoma, often results in retinal ganglion cell apoptosis and even necrosis, exacerbating optic nerve damage (9)(10)(11). Studies have unraveled that (12,13) inflammation and cell apoptosis are vital pathological reactions in acute high intraocular high pressure, and in acute high intraocular pressure injury, high intraocular pressure-induced vascular injury and other damage factors cause the increase in the release of local inflammatory factors and other cytokines in the optic nerve.…”
Section: Content Of Il-6 and Tnf-α Determined Using Elisamentioning
confidence: 99%